KUALIFIKASI USAHA PEMBENTUKAN BAITUL MAAL WAT TAMWIL (BMT) DI DESA SUKARAMI KECAMATAN KEDURANG ILIR KABUPATEN BENGKULU SELATAN - Lestari, Anita Fuji (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
This research aims to evaluate the feasibility of establishing BMT as a sharia microfinance institution that can improve community welfare. This research uses a qualitative method with a descriptive approach, involving interviews with BMT administrators, micro business actors and community leaders, as well as field observations. The research results show that the people of Sukarami Village really need financial access that is in accordance with sharia principles, considering the difficulties they face in obtaining loans from conventional financial institutions. From the analysis carried out, it was found that establishing a BMT in this village is not only legally and economically feasible, but also has the potential to empower micro-entrepreneurs through the provision of capital and training programs. Regulatory support from the government also provides a strong foundation for the establishment of BMT. Thus, the existence of BMT is expected to improve the economic welfare of the Sukarami Village community and reduce dependence on usury-based lending practices. This research recommends the need for further socialization of sharia financial products as well as collaboration with related parties to maximize the benefits of BMT for society.